Optimism and Self Compassion as Predictors of Resilience in College Students - Hidayat, Novi; Ikromi, Ziyadi Ali; Putro, Febrianur Ibnu Fitroh Sukono; Rahmawati, Sisca Dian; Rahayu, Hilda Sri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
Resilience is a dynamic and diverse process where individuals show psychological functioning despite unpleasant events (trauma). Resilient individuals can use personal abilities to deal with difficult situations and are influenced by the belief held by individuals that every problem can be solved with good results. This is inseparable from understanding within the individual not to judge anyone when dealing with issues. This study aims to show optimism and self-compassion as predictors of resilience in students. The research sample comprised 97 students from a private university in Palembang, Indonesia, who were 18-21 years old and was obtained by a multistage random sampling technique. Research data were obtained by filling out three adaptation scales, namely the Connor-Davidson Resilience Scale, Self-Compassion Scale, and Optimism Scale. Data analysis used multiple regression analysis techniques. Cronbach's Alpha coefficient reliability for Connor-Davidson Resilience Scale (0.824), Self-Compassion Scale (0.927), and Optimism Scale (0.775). The research results show optimism and self-compassion as predictors of resilience in students